From Radio Broadcasting to Livestream: Genres, Roles, and Inclusion Standards at Radio Galega: gêneros, funções e padrões de inclusão na Rádio Regional da Galiza - Gómez López, Concepción (Historia y Comunicación Social, 2026)
Since November 2024, Galician public broadcasting has been testing a “radiovision” format that synchronizes audio and video streaming (web, social media, and DTT). This article evaluates whether the visual dimension increases the average listening-viewing time, comparing EGM data with digital interaction metrics. Methodologically, audience analysis is combined with a quantitative-qualitative content analysis of 42 broadcasts (103 hours) aired between January and March 2025, taking into account the genders, roles, and characteristics of the presenters, sound/visual resources, guests, speaking turns, and use of inclusive language. The findings discuss the redefinition of the radio experience and the challenges of gender representation and accessibility.
Keywords: radiovision; broadcasting; public service; accessibility; gender representation